Achieving euthyroidism in hypothyroid patients using levothyroxine improves depressivity and impaired daily life scores using ThyPRO questionnaire - Tamer M Elsherbiny (SpringerOpen, 2019)
Background Levothyroxine is the recommended treatment to achieve euthyroidism in hypothyroid patients. Achieving euthyroidism was found to improve quality of life in some studies but failed to do so in other studies. Thyroid patient reported outcomes (ThyPRO) is a thyroid-specific health-related quality of life measure. This study aims to assess patient-reported outcomes in levothyroxine-treated hypothyroid patients using ThyPRO. Patients and methods The study included 194 patients, divided into two groups: group 1 included 141 hypothyroid patients with benign thyroid disease treated with l-thyroxine, stable in euthyroidism for at least 6 months, and group 2 included 53 patients with euthyroid benign thyroid disease. All patients completed a professionally translated, carefully revised version of the ThyPRO questionnaire into Arabic language. All patients had their Thyroid stimulating hormone (TSH) measured at inclusion. Anti-thyroperoxidase and/or anti-thyroglobulin antibodies were recorded for each patient where available. Results There were no significant differences between the two studied groups regarding age, sex, and TSH. Anti-thyroperoxidase antibodies were significantly higher in treatment group versus group 2, but anti-thyroglobulin antibodies did not differ among the two studied groups. Group 1, l-thyroxine treatment group, showed significantly lower scores in the goiter symptoms, depressivity, impaired daily life, and hyperthyroid symptom scales compared with group 2. No significant differences were found regarding the remaining symptom scales. Conclusion Hypothyroid patients of different etiologies rendered euthyroid for at least 6 months compared with euthyroid patients with benign thyroid disease have significantly better depression, goiter, impaired daily life scores using a thyroid-specific questionnaire, the ThyPRO, compared with euthyroid benign thyroid disease.